Native forced labour. (Item on agenda of 1929, International Labour Conference) (International Federation of Trade Unions, 1929)
First publ.: The International Trade Union Movement. 1928, Oct., Nov., Dec. and 1929, Jan., Febr. PAMPHLET VOLUME.